The contrary functions of lncRNA HOTAIR/miR‐17‐5p/PTEN axis and Shenqifuzheng injection on chemosensitivity of gastric cancer cells - Jia, Jianguang; Zhan, Dankai; Li, Jing; Li, Zhixiang; Li, Hongbo; Qian, Jun (Journal of cellular and molecular medicine, 2019)
This study was implemented to figure out whether lncRNA HOTAIR/miR‐17‐5p/PTEN axis played a role that was opposite to Shenqifuzheng (SQFZ) injection in regulating the chemosensitivity of gastric cancer cells. The gastric cancer tissues were gathered and four gastric cancer cell lines were prepared, including BGC‐823, MGC‐803, SGC‐7901, and MKN28. Moreover, cisplatin, adriamycin, mitomycin, and 5‐fluoroura were managed as the chemo‐therapeutics, and SQFZ was prepared as a Chinese medicine. Striking distinctions of HOTAIR, miR‐17‐5p, and PTEN expressions were observed between gastric cancer tissues and para‐carcinoma normal tissues (P < 0.05). MKN28 was associated with the highest resistance to cisplatin, adriamycin, mitomycin, and 5‐fluoroura among all the cell types, and SQFZ significantly improved the MKN28 cells’ sensitivity to the drugs (P < 0.05). The over‐expressed HOTAIR and miR‐17‐5p, as well as under‐expressed PTEN tended to significantly facilitate the viability, EMT process and proliferation of MKN28 cells that were subject to treatment of chemo‐therapies (P < 0.05). SQFZ could amplify the effects of si‐HOTAIR, miR‐17‐5p inhibitor, and pcDNA‐PTEN on boosting the chemosensitivity of gastric cancer cells (P < 0.05). In addition, HOTAIR was also found to directly target miR‐17‐5p, and PTEN appeared to be subject to the modification of HOTAIR and miR‐17‐5p in its acting on the viability, proliferation, EMT process, and apoptosis of gastric cancer cells. The HOTAIR/miR‐17‐5p/PTEN axis could be regarded as the potential treatment targets for gastric cancer, and adjuvant therapy of SQFZ injection could assist in further improving the treatment efficacy of chemo‐therapies for gastric cancer.